Evaluation of a 1540-nm and a 1410-nm Nonablative Fractionated Laser for the Treatment of Striae. Issue 2 (February 2016) - Wang, Krystle; Ross, Nicholas; Osley, Katie; Sahu, Joya; Saedi, Nazanin
Abstract : BACKGROUND: Aesthetically, striae distensae (SD) are a source of great concern. No treatment modality is currently considered the gold standard. However, studies of nonablative fractionated lasers (NAFLs) have been promising. OBJECTIVE: To evaluate and compare the clinical and histopathologic efficacy and safety of a 1540-nm NAFL and a 1410-nm NAFL for the treatment of SD. METHODS AND MATERIALS: Nine patients with abdominal striae were treated for 6 sessions—half of the abdomen was treated with a 1540-nm NAFL whereas the other half was treated with a 1410-nm NAFL. Photographs were taken at baseline and at the 3-month follow-up visit, when subjects were given a questionnaire. Two blinded dermatologists scored the photographs using a pre-established clinical scale. Biopsies were taken from 2 subjects and graded by 2 dermatopathologists using a pre-established pathology scale. RESULTS: All 9 subjects demonstrated clinical improvement bilaterally after treatment. Skin biopsies after treatment showed an increase in epidermal thickness, dermal thickness, and collagen and elastin density when compared with baseline. Clinical and histopathological differences between the 2 lasers were not statistically significant. CONCLUSION: Treatment with both the 1540-nm and the 1410-nm NAFL was shown to improve SD clinically and histopathologically. Further studies are needed to optimize treatment parameters.